PENGELOLAAN PEMBELAJARAN PAUD DALAM MENGEMBANGKAN POTENSI DIRI ANAK USIA DINIPADA WILAYAH KECAMATAN SA’DAN, TORAJA UTARA - Santi Santi; Novita Matalangi’, Crismaya Padang Allo, Sisilia Desmawati Rara’ Bulaan, George Mangande (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
Potential is the most important part of a child. With potential, individuals will feel valuable in their lives. Therefore, the purpose of this study is to find the potential in a child in the Sa'dan sub-district, especially in early childhood education, and also aims to find models that can be applied to develop this potential in a simple and easily recognized framework for children. To achieve this purpose, the research method used by the author is a qualitative method with a descriptive approach to describe the reality and reality that occurs in the Sa'dan sub-district related to the situation and context of early childhood education. Several theories that are the basis for the author's research are theories about children, children's potential and learning theories that come from literature and articles on social media. The results of this study are that the management of learning for early childhood with their potential is by giving a form of respect or appreciation for the child, opening up space to develop the potential of each child and becoming a parent for them who is full of love and care